A signature motif mediating selective interactions of BCL11A with the NR2E/F subfamily of orphan nuclear receptors - Chan, Chun Ming; Fulton, Joel; Montiel-Duarte, Cristina; Collins, Hilary M.; Bharti, Neetu; Wadelin, Frances R.; Moran, Paula M.; Mongan, Nigel P.; Heery, David M. (Oxford University Press, 2013)
Despite their physiological importance, selective interactions between nuclear receptors (NRs) and their cofactors are poorly understood. Here, we describe a novel signature motif (F/YSXXLXXL/Y) in the developmental regulator BCL11A that facilitates its selective interaction with members of the NR2E/F subfamily. Two copies of this motif (named here as RID1 and RID2) permit BCL11A to bind COUP-TFs (NR2F1;NR2F2;NR2F6) and Tailless/TLX (NR2E1), whereas RID1, but not RID2, binds PNR (NR2E3). We confirmed the existence of endogenous BCL11A/TLX complexes in mouse cortex tissue. No interactions of RID1 and RID2 with 20 other ligand-binding domains from different NR subtypes were observed. We show that RID1 and RID2 are required for BCL11A-mediated repression of endogenous γ-globin gene and the regulatory non-coding transcript Bgl3, and we identify COUP-TFII binding sites within the Bgl3 locus. In addition to their importance for BCL11A function, we show that F/YSXXLXXL/Y motifs are conserved in other NR cofactors. A single FSXXLXXL motif in the NR-binding SET domain protein NSD1 facilitates its interactions with the NR2E/F subfamily. However, the NSD1 motif incorporates features of both LXXLL and FSXXLXXL motifs, giving it a distinct NR-binding pattern in contrast to other cofactors. In summary, our results provide new insights into the selectivity of NR/cofactor complex formation.